2023
DOI: 10.1021/jacs.3c03112
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Atmospheric Halogen Cycling through Aqueous-Phase Oxygen Atom Chemistry

Abstract: Halogen atoms are important atmospheric oxidants that have unidentified daytime sources from photochemical halide oxidation in sea salt aerosols. Here, we show that the photolysis of nitrate in aqueous chloride solutions generates nitryl chloride (ClNO2) in addition to Cl2 and HOCl. Experimental and modeling evidence suggests that O­(3P) formed in the minor photolysis channel from nitrate oxidizes chloride to Cl2 and HOCl, which reacts with nitrite to form ClNO2. This chemistry is different than currently acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Based on the present measurements, it is not clear whether this occurs in surface waters (such as holding ponds or storage tanks) or in aerosols (such as droplets or aerosols generated during fluid usage and pumping). This mechanism would be consistent with studies , that have shown that photoactive processes can drive inorganic halogen formation in chloride-containing aerosols of different compositions. However, due to the variable and proprietary water compositions, we are unable to point to a specific photoactive agent that may initiate Cl 2 formation.…”
Section: Resultssupporting
confidence: 92%
“…Based on the present measurements, it is not clear whether this occurs in surface waters (such as holding ponds or storage tanks) or in aerosols (such as droplets or aerosols generated during fluid usage and pumping). This mechanism would be consistent with studies , that have shown that photoactive processes can drive inorganic halogen formation in chloride-containing aerosols of different compositions. However, due to the variable and proprietary water compositions, we are unable to point to a specific photoactive agent that may initiate Cl 2 formation.…”
Section: Resultssupporting
confidence: 92%
“…Enhanced production of HONO by an energy transfer mechanism through organic chromophores can potentially contribute to the missing budget for daytime HONO production. Furthermore, this study expands our understanding of nitrate photochemistry within single aqueous droplets, an active area of research that has recently shown some additional aspects of nitrate photochemistry including the importance of the role of excited states, and aqueous aerosol size, as well as the impact on halogen cycling for this reaction …”
mentioning
confidence: 85%
“…For only four stations, the simulated difference in the concentration is slightly higher than a factor of two. insoluble and efficiently transfer chlorine to the gas phase (Soni et al, 2023;Dalton et al, 2023). The aerosol pH is defined as the negative decimal logarithm of the hydrogen ion activity (a H + ):…”
Section: Ammonium (Nh + 4 )mentioning
confidence: 99%
“…However, model studies are usually limited to the representation of relevant chemistry by using surface reactions uptake coefficients with little dependence on aerosol composition. In AERCHEM, key reactions for the production of HONO, ClNO 2 and Cl 2 can now be investigated by incorporating the recent advancements on the multiphase kinetics of chlorine (Soni et al, 2023;Dalton et al, 2023).…”
Section: Crustal Elementsmentioning
confidence: 99%